Performance of Inboard Diesel Engine Fitted Canoes Operating Ring Seine along Kerala Coast - B., Madhusoodana Kurup; Rajasree, Radhika (Fishery Technology, 2025)
The performance of the recently introduced Inboard Engine(IBE) fitted crafts operating ring seine is reported. 153 units were enumerated from 8 districts of Kerala. The total landing from IBE canoes was found to be 11745 tonnes, with an average catch per unit effort of 1826 kg and average catch per hour 555 kg. The operation cost and revenue generated from ring seine operated by Out Board Motor canoes and IBE canoes are compared.